2002
DOI: 10.1097/00005537-200205000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Association of Laryngopharyngeal Symptoms With Gastroesophageal Reflux Disease

Abstract: Laryngopharyngeal symptoms can be predictors of gastroesophageal diseases and GERD because the most frequent underlying cause is supposed to be associated with posterior laryngitis. Medical antireflux treatment is effective for relief of symptoms and mucosal healing of posterior laryngitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 35 publications
9
86
0
7
Order By: Relevance
“…In the past, Koufman described posterior laryngitis in 74% and laryngeal edema with erythema in 60% of all patients with GERD [16] . Tauber et al also reported 85% of GERD-positive patients had posterior laryngitis and 69% had laryngitis with an interarytenoid erythema and edema [22] . Our prevalence rate of LPR is much lower than theirs; the different sample size of patients and method of enrollment in our research must have influenced the results.…”
Section: Discussionmentioning
confidence: 93%
“…In the past, Koufman described posterior laryngitis in 74% and laryngeal edema with erythema in 60% of all patients with GERD [16] . Tauber et al also reported 85% of GERD-positive patients had posterior laryngitis and 69% had laryngitis with an interarytenoid erythema and edema [22] . Our prevalence rate of LPR is much lower than theirs; the different sample size of patients and method of enrollment in our research must have influenced the results.…”
Section: Discussionmentioning
confidence: 93%
“…Esse movimento oposicional brusco, realizado de maneira frequente, inicialmente leva a um edema localizado que, posteriormente, por hialinização e fibrose, torna-se firme 1,31,36 . Outros fatores têm sido citados na origem dos nódulos vocais, como anomalias anatômicas da laringe (micromembrana em comissura laríngea anterior) 29,30 , refluxo gastroesofágico 39 , distúrbios hormonais, e os fatores psicoemocionais 40 . Dessa forma, pode-se dizer que a origem dos nódulos é multifatorial 7,15,36,41 .…”
Section: Nódulos Vocaisunclassified
“…A maioria dos pacientes do grupo DRE apresentava esofagite grau I, sem diferença signifi cativa em relação às queixas (Tabela 5). (27) . Em uma grande série (n = 1 511) foi demonstrado que, pelo menos, uma manifestação atípica estava presente em 80% dos pacientes que se apresentavam com sintomas típicos de refl uxo (15) .…”
Section: Resultsunclassified